Potensi Pengembangan Objek Wisata Halal Dan Pengaruh Terhadap Pendapatan UMKM Di Desa Bukit Kabupaten Bengkalis - Dasio, Muhammad (Jurnal Rumpun Ilmu Ekonomi, 2024)
One of the important steps related to tourism development is the identification study of potential tourist attractions. This is important because a tourist trip to a place is basically influenced by tourists' interest in something called a tourist attraction or attraction. To develop it requires a special strategy using attractiveness, facilities, accessibility, promotion and location. The potential for developing a halal tourism village is considered to be able to increase the MSMEs of the Bukit Batu Village community, besides that Bukit Batu Village also has an interesting history that is always discussed, it also has various existing tourism potentials. This study uses the correlation method, namely the method by connecting the selected and explained variables and aims to examine the extent to which variables in a factor are related to other variables. From the results of this research analysis, it is known that the calculated f value is 16.169 and the Ftable value is 2.20 which explains that the value of f = 16.169> 2.20 and the significance value <0.05 (0.00 <0.05). So it can be concluded that the variables of attractiveness, facilities, accessibility, promotion and location location together have an effect on MSME income. And for the Adjudted R square value of 0.434 which indicates that changes in Attractiveness (X1), Facilities (X2), Accessibility (X3), Promotion (X4), and Location (X5) on Revenue (Y) are influenced by 46.2% which means that simultaneously the variables of attractiveness, facilities, accessibility, promotion and location have an effect on MSMEs in Bukit Batu Tourism Village.